2007
DOI: 10.1016/j.yexcr.2007.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of phosphoinositide 3-kinase cause defects in the postendocytic sorting of β2-adrenergic receptors

Abstract: Phosphatidylinositol 3-kinase inhibitors have been shown to affect the endocytosis or subsequent intracellular sorting in various receptor systems. Agonist-activated β 2 -adrenergic receptors undergo desensitization by mechanisms that include the phosphorylation, endocytosis and degradation of receptors. Following endocytosis, most internalized receptors are sorted to the cell surface, but some proportion is sorted to lysosomes for degradation. It is not known what governs the ratio of receptors that recycle v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Consistent with these observations, the involvement of PI3K is implicated in P2Y purinergic receptor resensitization [114, 115]. The role of PI3K in resensitization is increasingly evident by defects caused by PI3K inhibitors in postendocytic sorting of β 2 -adrenergic receptors [116]. …”
Section: Gpcr Resensitizationmentioning
confidence: 80%
“…Consistent with these observations, the involvement of PI3K is implicated in P2Y purinergic receptor resensitization [114, 115]. The role of PI3K in resensitization is increasingly evident by defects caused by PI3K inhibitors in postendocytic sorting of β 2 -adrenergic receptors [116]. …”
Section: Gpcr Resensitizationmentioning
confidence: 80%
“…Several components of this machinery require 3-phosphorylated phosphoinositides for membrane attachment (Cullen and Korswagen, 2011), and a previous study (Awwad et al, 2007) Vps34 represents an endosomal target that controls b2AR signaling. Chemical inhibitors used in previous studies of b2AR trafficking (Sorensen et al, 1999;Naga Prasad et al, 2001;Awwad et al, 2007) [wortmannin (WM) and LY294002] have additional cellular targets (Knight, 2010). In the current study, we employed more specific manipulations to examine the trafficking and signaling effects of endosomal PI3P and Vps34, and revealed previously unrecognized roles of this critical endosomal kinase in GPCR signaling.…”
Section: Introductionmentioning
confidence: 82%
“…b2-adrenoceptors internalize rapidly after ligand-induced activation via clathrin-coated pits and have the ability to recycle to the PM with remarkably high efficiency via a retromer-dependent pathway (Goodman et al, 1996;Temkin et al, 2011). Several components of this machinery require 3-phosphorylated phosphoinositides for membrane attachment (Cullen and Korswagen, 2011), and a previous study (Awwad et al, 2007) Vps34 represents an endosomal target that controls b2AR signaling. Chemical inhibitors used in previous studies of b2AR trafficking (Sorensen et al, 1999;Naga Prasad et al, 2001;Awwad et al, 2007) [wortmannin (WM) and LY294002] have additional cellular targets (Knight, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The 22-h treatment time was chosen to insure that receptor levels were at steady state between degradation and synthesis. Previous work with this cell line indicated that receptor degradation approaches maximum at approximately eight after addition of agonist (Awwad et al 2007). …”
Section: Resultsmentioning
confidence: 78%